Is there still a role for alveolar recruitment maneuvers in acute respiratory distress syndrome? - Kallet, Richard H.; Lipnick, Michael S. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
An alveolar recruitment maneuver (ARM) involves the transient application of high transpulmonary pressures to achieve threshold opening pressures in collapsed peripheral airways and alveoli. The expectation of ARMs is to improve oxygenation, lung compliance and potentially facilitate alveolar fluid clearance (1,2). Although the origins of ARM as a clinical tool were for treating intra- or post-operative atelectasis (3), beginning in the 1990’s ARM became a central feature of “open-lung ventilation” (OLV), a lungprotective ventilation strategy for managing patients with acute respiratory distress syndrome (ARDS) (4).